Collocations with High Frequency Verbs in Learner English: Lithuanian Learners vs Native Speakers - Juknevičienė, Rita (Kalbotyra, 2008)
[full article, abstract in English; abstract in Lithuanian] Analysis of learner language, or interlanguage, produced by learners of different mother tongues has many implications for the theory and practice of teaching/learning English as a foreign language (EFL). The aim of the present research is to analyse collocational competence, of Lithuanian learners of English. The study was designed as a pilot study to analyse the learners’ ability to produce collocations with high-frequency verbs, i.e. HAVE, DO, MAKE, TAKE and GIVE, and compare it with data from a comparable corpus of native speakers of English. It is assumed here that similar studies can shed light on the specific difficulties that Lithuanian learners of English face and contribute to the enhancement of teaching and learning outcomes. [...]